Notary's Authority To Publish Deeds - Udin Narsudin (Jurnal Multidisiplin Sahombu, 2024)
In order to determine heirs to ensure legal certainty, the Notary is the only party who has the authority to issue birth certificates for all Indonesian citizens regardless of their ethnic origin. This is based on the UUJN (Notary Public Law) which regulates that notaries have the authority to determine evidence in the form of public documents, including heir statements . Notaries are appointed by law as the sole owner or institution that has the right to issue Notaries for all Indonesians, as intended in Article 15 paragraph. (1) UUJN, based on the Notary's authority to determine the actual deed. The authority of a Notary is personal authority and its function itself must have legal meaning, be binding, so that its function can run well and does not conflict with the authority of other functions. Issuance of inheritance deeds by a notary to all Indonesian citizens without discrimination in accordance with legal principles and upholding laws regarding safety and equality before the law. Likewise, the Notary's right to provide evidence as an heir or as a statement of heir is protected by the UUJN, a step that is in line with the concept of development law.